THE EDUCATIONAL VALUES ANALYSIS OF THE BESTSELLING BOOK “RICH DAD, POOR DAD”BY ROBERT T. KIYOSAKI - Prawira Yustisyo, R. Arryo (Department of English Education, Universitas Panca Sakti Bekasi, 2024)
Rich Dad, Poor Dad by Robert T. Kiyosaki has garnered widespread attention and acclaim since its publication, becoming a cornerstone in the world of educational value in the context of literature. This research aims to conduct a comprehensive analysis of the educational values embedded within the pages of this best-selling book. Through a qualitative examination of the book's content, themes, and instructional methodologies, this study seeks to identify and evaluate the key educational principles advocated by Robert T. Kiyosaki. Furthermore, it aims to explore the practical implications of these principles on readers' educational values, mindset, and behavior. Drawing upon relevant educational theories and frameworks, such as experiential learning and value-based learning, this research will provide insights into the book's effectiveness as an educational tool. Additionally, it will examine category of the educational values and collections of selected texts surrounding Kiyosaki’s teachings, addressing concerns related to 18 educational ethics released by Indonesian Ministry of Education, educational value disparities, and the applicability of his advice across diverse contexts. Ultimately, this research contributes to the ongoing discourse of value-based education and personal development literature, offering a nuanced understanding of the educational values encapsulated within the book Rich Dad, Poor Dad by Robert T. Kiyosaki and its impact on readers' educational knowledge and practices.